Seismotectonic analysis of the 2013 seismic sequence at the western Corinth Rift - G. Chouliaras; Kassaras, I.; V. Kapetanidis; P. Petrou; Drakatos, G. (Journal of Geodynamics, 2015)
This study focuses on a series of small intraplate earthquakes that took place during May–August 2013 on the southwestern coast of the Corinth Rift (Central Greece), a few km southeast of Aigion city. The Corinth Rift is one of the most seismically active parts of the Mediterranean. We analyzed more than 1500 events with 0.4≤ML≤3.7, the major part of which was recorded by a dense local network. The seismicity is densely clustered in a volume of dimensions ∼4×2×6km3, aligned in a N110° direction and at depths ranging between 6 and 12km. Precisely relocated hypocenters and reliably constrained focal mechanisms indicate north dipping planar faults with an average dip of ∼60°. Stress inversion of focal mechanisms implies that the dominant local stress field is extensional in a N5° direction, in good agreement with geodetic observations. The swarm evolved in two phases, with a spatiotemporal migration of epicenters from the eastern toward the western part of the rupture zone, while slip distribution appears homogeneous over the eastern part and strongly inhomogeneous in the western part. These two phases also produced different results in scaling relations such as the Gutenberg–Richter law, the Modified Omori Formula and the Epidemic Type of Aftershock Sequence model. Similar results from other studies have been reported and correlated with a fluid driven mechanism, however further research is required to strengthen this hypothesis for the purposes of this study.
Keywords: Corinth rift; Normal faulting; Seismic swarm; Seismotectonics; Spatiotemporal